Detection of Listeria innocua in the dairy processing chain: resistance to antibiotics and essential oils - da ROSA, Mayara Cardoso; Iacuzio, Raiza; Barbosa, Giovana Rueda; Pereira, Rodrigo de Castro Lisboa; Cruzado-Bravo, Melina; Rall, Vera Lucia Mores [UNESP]; Vallim, Deyse Christina; Silva, Nathália Cristina Cirone (FapUNIFESP (SciELO), 2022)
Listeria monocytogenes is a food pathogen responsible for many foodborne disease outbreaks. Listeria innocua is similar to L. monocytogenes, could be considered biologically similar to L. monocytogenes and could be used to predict its behavior. The aims of this work were to isolate Listeria spp. in dairy processing plants, perform genotypic characterization of virulence, evaluate the antimicrobial resistance profile, and verify the sensitivity of the strains to essential oils. Sampling was held in six dairy processing plants in the region of Campinas, Brazil. Seventeen Listeria innocua strains were isolated, all negative for virulence genes inlA, inlB, inlC, inlJ, actA, plcA, and plcB. The strains were resistant to kanamycin (5.9%), penicillin (11.8%), ampicillin (11.8%), cefoxitin (58.8%), clindamycin (76.50%) and oxacillin (100%). The susceptibility of the strains to commercial essential oils (Rosemarinus officinalis, Cymbopogon citratus, Eucalyptus citirodora, Mentha piperita, Piper nigrum, Vetiveria zizanioides, Cymbopogon nardus, Cymbopogon martinii and Pogostemon cablin) was evaluated by Minimum Inhibitory Concentration (MIC) test. The results showed Cymbopogon citratus, Cymbopogon martini, Cymbopogon nardus and Mentha piperita oils were most efficient. The resistance of Listeria innocua isolated in dairy processing plants is worrisome, and the use of essential oils could be an alternative for development of new drugs and products.
Keywords: dairy; food processing; food safety; Listeria infection; resistance